2009
DOI: 10.4103/0028-3886.53282
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of blood-cerebrospinal fluid barrier dysfunction during the course of Guillain Barré syndrome

Abstract: B-CSFB dysfunction was present in only half of the patients with GBS during the first week from onset and it was directly associated with progression and clinical severity; nevertheless, a low B-CSFB dysfunction response during follow-up was associated with a lethal outcome, suggesting it could also serve a 'protective' effect during regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…This fact can be explained because, unlike other arboviruses 2 , this virus rarely affects the central nervous system. The pathophysiology of these neurological complications can be explained by the occurrence of cerebral edema, cerebral hemorrhage, hyponatremia, liver failure associated with portasystemic encephalopathy, cerebral anoxia, microcapillary hemorrhage and/or the release of toxic products, which can occur separately or together 9 .…”
Section: Discussionmentioning
confidence: 99%
“…This fact can be explained because, unlike other arboviruses 2 , this virus rarely affects the central nervous system. The pathophysiology of these neurological complications can be explained by the occurrence of cerebral edema, cerebral hemorrhage, hyponatremia, liver failure associated with portasystemic encephalopathy, cerebral anoxia, microcapillary hemorrhage and/or the release of toxic products, which can occur separately or together 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Study done by Gonzalez-Quevedo et al revealed raised CSF total proteins correlated with the degree of inflammation at the nerve roots and higher level of CSF proteins were related to clinical severity [12]. Corston et al studied amino acids in CSF of GBS patients quantitatively as well as qualitatively.…”
Section: Discussionmentioning
confidence: 99%
“…Within the first week of symptoms, normal CSF protein levels can be expected in anywhere from 33%-52% of patients. 9,11 Likewise, early on in the disease course, the well-described electrophysiologic abnormalities of prolonged distal latencies, slowed conduction velocities, abnormal F-waves, and temporal dispersion and/or conduction block are not typically present in their entirety. [12][13][14] Although the precise reason for the characteristic cytoalbuminologic dissociation described in GBS is not completely understood, it is likely due to early nerve root involvement.…”
mentioning
confidence: 98%
“…14 With the premise that AIDP is a predominantly humorally mediated disease process, the CSF protein levels of patients with GBS can be used as a marker of BNB dysfunction. 7,9,10 Our retrospective review demonstrates that the degree of CSF protein elevation correlates with the number of electrophysiologic abnormalities on nerve conduction studies (NCSs) in patients with GBS.…”
mentioning
confidence: 99%
See 1 more Smart Citation